The Existence of Solutions for Second-order Differential Equations under Almost Fisher-Type Multivalued F-Contractions in Metric Spaces (European Journal of Pure and Applied Mathematics, 2025)
This paper presents novel fixed point (FP) theorems for a specific class of multivalued contractions, referred to as ”almost Fisher type multivalued F-contractions” within complete metric spaces (MSs) endowed with a Γ-transitive binary relation ℜ. These theorems establish the existence of FPs for such contractions and explore their intrinsic properties. Illustrative Examples are provided to demonstrate the applicability and effectiveness of the proposed results. An application for solving second-order differential inclusions (SODIs) is provided under these contractives.
Keywords: Fixed point; metric space; almost Jaggi-type contraction; binary relation; second-order differential equation